Demonstração: uma seqüência didática para a introdução de seu aprendizado no ensino da geometria - Mello, Elizabeth Gervazoni Silva de (1999)
The objective of this work consisted in developing a didactic sequence as a metodological alternative to teach geometry for the 8th grade students, with the aim to show them new ways of the deductive geometrical thought. With this purpose, we worked on a didactic sequence to introduce the demonstration tecnique, taking into consideration BALACHEFF, DUVAL and other french searchers theory. The activitie were adapted from BONNEFOND,D. & DAVIAND,D. & REVRANCHE,B.. We worked with a class of fourteen students from the 8th grade. We analysed all the difficulties during the sequence application, then discussed and suggested strategics to solve the activities. Tests were applied during as well as in the last session. We concluded that the way we worked our didactic sequence favoured the learning of the demonstration tecnique in geometry